Retention strength of monolithic zirconia crowns cemented with different primer-cement systems - Mohamed Shokry; Walid Al-Zordk; Mohamed Ghazy (BMC, 2022)
Abstract Background The purpose of this in vitro study was to assess the influence of different cement systems with different ceramic primers on the retention strength of zirconia crowns. Methods Thirty extracted molars were prepared with flat occlusal surfaces, 20 degrees taper, and 3 mm axial wall height. A zirconia crown with an occlusal bar was fabricated for each tooth. All specimens were divided (n = 10) into; Group M: Multilink Speed/Monobond N, Group P: Panavia V5/Clearfil Ceramic Primer Plus, Group D: Duo-Link universal/Z-Prime Plus. The intaglio surfaces of crowns were air-abraded using 50 µm alumina at 2.5 bar for 10 s. Then each crown was cemented onto its corresponding tooth. All specimens were thermocycled for 10,000 cycles between 5 and 55 °C. Each crown was subjected to gradually increasing vertical load along the path of insertion through hooks engaging the occlusal bar using a universal testing machine until failure. The force at dislodgment was recorded and retention strength was calculated for each specimen. The failure modes were recorded for each specimen. The data were statistically analyzed using one way ANOVA test followed by Tukey HSD test (α = .05). Results Group D showed lowest strength (1.42 ± 0.23 MPa) and differed significantly (P < .001) from Group M (2.71 ± 0.45 MPa) and Group P (2.47 ± 0.41 MPa). There was no significant difference (P = .34) between Group M and Group P. The failure modes for Groups M and Group P were mainly cohesive, while Group D showed adhesive failure. Conclusions The retention strength of zirconia crowns was improved with Multilink Speed and Panavia V5 cement systems, while the use of the Duo-Link Universal cement system only showed half of those retention strength values.